Faktor-faktor yang Memengaruhi Keberhasilan Studi Penerima Bidikmisi di Universitas Sultan Ageng Tirtayasa - Gina Fithria; Siti Amanah; Simanjuntak, Megawati (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study aims to analyze the influence of internal factors, external factors, service quality, and financial aid on the success of the study of Bidikmisi scholarship recipients at Sultan Ageng Tirtayasa University. The study used descriptive quantitative method with a retrospective survey approach. The sample of this study was 247 graduates of Bidikmisi recipients at Sultan Ageng Tirtayasa University. The data analysis technique used is Structural Equation Modeling (SEM) with LISREL software and Importance Performance Analysis (IPA). The results showed that internal, external, and service quality factors had a positive and significant relationship to the study's success, but financial aid did not affect the study's success. The indicator variable that best describes the internal factor is the academic self-concept, while for the external factor is the community environment, and for the service quality is responsiveness. Internal factors have the most significant influence on the success of the study of Bidikmisi recipients, while external factors have the least influence. It is advised to UNTIRTA to set their priority to increase the success of the study of Bidikmisi recipients by paying attention to internal factors, service quality, and external factors. Improving internal conditions is done by increasing academic interest and doing orientation at the beginning of the lecture. Improving the quality of service is done by improving the quality of information and the attitude of the manager's empathy, while improving external condition is done by completing studies with peer groups. Keywords: higher education management, SEM, success of study, bidikmisi, IPA